Ninachka: The Making of an Englishwoman? - Underwood, Jay (Hamilton Books, 2007)
This autobiography tells the story of an indefatigable spirit who survived the Second World War, a doomed marriage, the murder of her father, rape, and the almost endless consternation of family problems. Author Dr. Nina Murray was born in St. Petersburg, Russia in 1913. As a child, she found herself part of the first of the Diaspora that marked the modern age. The Communist revolution stripped her family, Russian nobility, of their land, money, privilege, and title. Blessed with parents who were determined to overcome the devastating reversal of their fortunes, she found herself in England in the 1920's. There, she began the transformation from Russian Princess to professional English woman, and earned her medical degree in 1937. On her journey, Murray finds her life's love in her work, her daughter and an eight-year marriage to a Canadian admiral, and crosses the paths of other fascinating lives_some very well-known, others quite outrageous. Dr. Murray's story offers a valuable lesson to immigrants in any country, at any age, and deals with the necessity of absorbing one's new surroundings while clinging to one's roots.